Metabolic changes during the transition period - A.F. Park; E.C. Titegemeyer; R.C. Cochran; J.M. DeFrain (Kansas Agricultural Experiment Station Research Reports, 2002)
We used four ruminally fistulated, multiparous, pregnant Holstein cows to measure changes in concentrations of plasma metabolite as the dairy cow transitions from one lactation to the next. Diets consisted of typical far-off and close-up diets, a late lactation diet containing wet corn gluten feed (20% DM), and an alfalfa hay-corn silage based early lactation diet. Calculated NEL (Mcal/lb), measured crude protein (%), and diet digestibilities (%; based on steers fed at 2% of BW) were 0.78, 18.7, 74.1; 0.70, 11.5, 66.2; 0.74, 15.6, 71.0; 0.73, 18.4, 70.7 for late lactation, far-off dry, close-up dry, and early lactation diets, respectively. Blood samples were obtained on day 79 prior to calving and weekly thereafter until calving and on days 1, 3, 5, 7, 15, 20, 25, 30, 60, and 90 after calving. Cows gained body weight and condition during the dry period, peaked just prior to calving, and lost weight and condition steadily through the first 11 weeks of lactation. Calculated energy balance was negative during the first 3 weeks of lactation. Plasma concentrations of non-esterified fatty acids (NEFA), glucose, and insulin to glucagon ratio remained fairly stable during the dry period. Plasma glucose increased just before calving, decreased markedly during early lactation, then increased and stabilized by day 30 of lactation. Plasma NEFA concentrations increased at calving and were elevated during early lactation, then returned to prepartum concentrations by day 30 of lactation. The insulin to glucagon ratio decreased just prior to calving, continued to decrease until day 7 of lactation, and then remained stable until the end of the trial. Changes in diet and intake affected plasma urea nitrogen, which decreased as dietary protein decreased during the far-off period, decreased with intake during the close-up period, and increased after calving consistent with the higher dietary protein and increase in dry matter intake. Most of the observed metabolic adaptations reflected the energy status of the cow with large shifts occurring around parturition. Certainly, some of the hormones associated with calving can initiate metabolic events favorable to lactation, but the changes in energy balance and nutrient supply support the continued diversion of nutrients to the mammary gland. These data support the concept that dairy cows experience a period of increased tissue mobilization from approximately 2 days prior to calving until 30 days after calving. In conclusion, a number of metabolic adaptations occur in transition dairy cows that provide clues to improve feeding and management guidelines.; Dairy Day, 2002, Kansas State University, Manhattan, KS, 2002;
Keywords: Dairy Day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-121-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 898; Dairy; Transition; Dairy cow; Plasma